How does supplementary green light and UV-radiation affect biomass and rutin content in Levisticum officinale? - Thoma, Felix; Schlehuber, Dennis; Somborn, Annette; Keuter, Volkmar (Frontiers in Sustainable Food Systems, 2024)
Due to several benefits regarding human health, the flavonoid rutin gains interest in nutrition and pharmaceutical industry. In order to satisfy high quality standards during cultivation and the final product, plants are grown increasingly in controlled environments with LED-technology as artificial light source. In this study the effect of various light settings on rutin content and biomass of Levisticum officinale was investigated. For continuous tracking of the biomass during cultivation, RGB-Images were taken. The actual biomass after harvest showed a strong positive correlation with the number of leaf-pixels detected via image processing (R2 = 0.937). Concerning the effect of UV-B radiation on rutin synthesis, time of synthesis was investigated. Two days after UV-B treatment a significant increase in rutin was observed. A short exposure time in combination with a high irradiance of 1 W m2 also showed positive effects on the rutin content in lovage. No significant effect of UV-B light on fresh weight was shown, but the combination of supplementary green light and high total photosynthetic photon flux density (PPFD) resulted in an increase of biomass.